Management and Outcome of Urogenital Trauma in Tertiary Hospital: The 8-Year’s Experience in Indonesia - Azmi, Yufi Aulia; Renaldo, Johan (Open Access Macedonian Journal of Medical Sciences, 2022)
Introduction: The current economy, technology, and civilization’s development have indirectly increased the incidence of traffic accidents, and urogenital trauma occurs in 10-20% of trauma patients. We decided to conduct this study to determine the incidence, severity, and outcome of urogenital trauma treatment at Dr Soetomo General Hospital Surabaya. Material and Method: This study used an analytic observational study with a retrospective design. From 2013 to 2020, all medical record data of patients with urogenital trauma treated at Dr. Soetomo General Hospital Surabaya were collected and analyzed. Result: We collected 196 subjects with urogenital trauma who were treated for a period of 8 years. The most common type of trauma in urogenital trauma patients was kidney trauma, as many as 82 cases. Most of the cases were traffic accident cases, 184 patients and most of them with abdominal-pelvic trauma with 189 findings. Conservative management was most often performed, as many as 128 procedures. The outcome after receiving treatment was found to be that 27 patients died (13.8%) and 11 patients (6.5%) had a disability. Abdominal trauma was associated with external genitalia, urethra, and renal trauma (p < 0.05). External genitalia, urethra, bladder, and renal trauma were all associated with pelvic trauma (p < 0.05). Conclusion: Most cases were caused by accidents, and the kidney was the most commonly involved organ. Cases of urogenital trauma are often associated with multiple trauma, especially abdominal trauma, so it is important to evaluate the urogenital tract when related to accidents involving the abdominal region